PENGARUH KOMUNIKASI DAN MOTIVASI KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA DINAS PERHUBUNGAN MUSI BANYUASIN - Ika Rakhmalina; Avissa Calista (Jurnal Manajemen Kompeten, 2019)
The purpose of this research is to understand the influence communication andmotivation work to performance state civil apparatus. Reveal and analyze the empiricalfacts, in order to know how communication is done and work motivation performanceagainst the state civil apparatus. This study uses a quantitative analytical researchdesign. The study population was the entire apparatus of state civil Banyuasin DistrictDepartment of Transportation. The study authors use a sampling technique that thecensus technique, in which the entire study population sampled, so the number of samplesin this study were 50 civilian state apparatus. Based on the analysis based on the resultsof analysis on the obtained value of regression testing F-hitung 30.981 (30.981 F count>F-table 3.20), the level of significance together independent variables to the dependentvariable, namely 0,000 (sig F = 0.000 <α 0.05). This result proves the communicationand motivation to work together have real influence / significantly to the performance ofcivil state apparatus 56.9% against the performance of employees in providing services,and the remaining 43.1% of the state civil apparatus performance is influenced by otherfactors. This proves the better communication and motivation will increase performanceof the apparatus of civil state in providing services to the people within the Departmentof Transportation Musi this Banyuasin.